Perceptual symbols of creativity: Coldness elicits referential, warmth elicits relational creativity - IJzerman, Hans (Institutional Knowledge at Singapore Management University, 2014)
Research in the cognitive and social psychological science has revealed the pervading relation between body and mind. Physical warmth leads people to perceive others as psychological closer to them and to be more generous towards others. More recently, physical warmth has also been implicated in the processing of information, specifically through perceiving relationships (via physical warmth) and contrasting from others (via coldness). In addition, social psychological work has linked social cues (such as mimicry and power cues) to creative performance. The present work integrates these two literatures, by providing an embodied model of creative performance through relational (warm = relational) and referential (cold = distant) processing. The authors predict and find that warm cues lead to greater creativity when 1) creating drawings, 2) categorizing objects, and 3) coming up with gifts for others. In contrast, cold cues lead to greater creativity, when 1) breaking set in a metaphor recognition task, 2) coming up with new pasta names, and 3) being abstract in coming up with gifts. Effects are found across different populations and age groups. The authors report implications for theory and discuss limitations of the present work.